Regulatory effect of inositol on the synthesis of myo-inositol-1-phosphate synthase in Neurospora crassa strains. - A Zsindely; A. Kiss; M. Schablik; M. Szabolics; G. Szabo. (Fungal Genetics Reports, 1982)
Regulatory effect of inositol on the synthesis of myo-inositol-1-phosphate synthase in Neurospora crassa strains.